2004
DOI: 10.1111/j.1365-2265.2004.02139.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure to normalize parathyroid hormone during treatment of vitamin D deficiency in Asian patients

Abstract: This study has demonstrated that long-term oral treatment with vitamin D and calcium, fails to normalize PTH in a significant proportion of patients with vitamin D deficiency and osteomalacia. This is most likely related to lack of adherence to long-term treatment. Improved ways of treating this condition need to be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…16,19,20 In addition, the commonly used doses of vitamin D (400-800 IU daily) may fail to improve 25(OH)D levels substantially in older adults with vitamin D deficiency and fail to normalize PTH. [20][21][22][23] Although it is commonly assumed that sHPTH is simply a matter of inadequate vitamin D intake that responds promptly to the supplementation of vitamin D, the optimal dose of vitamin D needed to normalize PTH is unknown. 20 A recent trial demonstrated that the dose-response curve of serum 25(OH)D concentration to cholecalciferol supplementation is widely variable, suggesting that people may respond differently, in terms of serum 25(OH)D increases, to a fixed dose of cholecalciferol.…”
mentioning
confidence: 99%
“…16,19,20 In addition, the commonly used doses of vitamin D (400-800 IU daily) may fail to improve 25(OH)D levels substantially in older adults with vitamin D deficiency and fail to normalize PTH. [20][21][22][23] Although it is commonly assumed that sHPTH is simply a matter of inadequate vitamin D intake that responds promptly to the supplementation of vitamin D, the optimal dose of vitamin D needed to normalize PTH is unknown. 20 A recent trial demonstrated that the dose-response curve of serum 25(OH)D concentration to cholecalciferol supplementation is widely variable, suggesting that people may respond differently, in terms of serum 25(OH)D increases, to a fixed dose of cholecalciferol.…”
mentioning
confidence: 99%
“…However, that does not appear to be the case in all patients. In a study of Asian patients with vitamin D deficiency, PTH normalized only in 45-55% subjects [23]. In another study of secondary hyperparathyroidism in patients with osteoporosis, Yendt, et.…”
Section: Discussionmentioning
confidence: 99%
“…south Asians, people aged over 65 years and living alone) may require higher doses (e.g. 20µg [800 IU] daily) 24–26…”
Section: Preventing Vitamin D Deficiencymentioning
confidence: 99%